Swearing and Its Motives in the Antologi Rasa Novel: (Retracted due to Double Publication) - Adityo Prawinanto; Hardi Prasetyo; Barli Bram (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2019)
This paper is retracted by editor due to double publication at https://jurnal.uin-antasari.ac.id/index.php/let/article/view/3593